2020
DOI: 10.3892/etm.2020.8645
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of abnormal iron distribution in specific regions in the brains of patients with Parkinson's disease using quantitative susceptibility mapping and R2* mapping

Abstract: The primary aim of the present study was to evaluate abnormal iron distribution in specific regions of the brains in patients with Parkinson's disease (PD) using quantitative susceptibility mapping (QSM) and R2 * mapping, and to compare the diagnostic performances of QSM and R2 * mapping in differentiating patients with PD with that in normal controls. A total of 25 patients with idiopathic PD and 28 sex-and age-matched normal controls were included in the present study and their brains investigated using a 3T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 53 publications
9
19
0
Order By: Relevance
“…This shows the close relationship between PD and iron deposition in the SN pars compacta. Similar findings show that QSM has a higher diagnostic performance than R2* mapping in patients with PD (74,90,91). Notably, patients with early PD showed higher susceptibility values in the bilateral SN on QSM images.…”
Section: Qsm In Pdsupporting
confidence: 76%
“…This shows the close relationship between PD and iron deposition in the SN pars compacta. Similar findings show that QSM has a higher diagnostic performance than R2* mapping in patients with PD (74,90,91). Notably, patients with early PD showed higher susceptibility values in the bilateral SN on QSM images.…”
Section: Qsm In Pdsupporting
confidence: 76%
“…Increased iron, copper and manganese concentrations in the substantia nigra were reported in a mouse model of experimental Parkinsonism (Matusch et al, 2012). Several other studies also reported significantly increased iron concentrations in the substantia nigra of PD patients compared to healthy controls by quantitative susceptibility mapping (Langkammer et al, 2016;Wang et al, 2016;Chen et al, 2019;Cheng et al, 2020). In a study of patients with neurodegeneration with brain iron accumulation (NBIA), thalamic and mesencephalic iron accumulation was also detected (McNeill et al, 2012).…”
Section: Discussionmentioning
confidence: 90%
“…Previous research has demonstrated iron accumulation in the brain of PD patients [ 13 , 14 ] and MPTP-treated mice [ 15 , 16 ]. Increased iron concentrations can induce oxidative stress through ROS generation and cause neuronal damage [ 15 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%